2006
DOI: 10.1111/j.1439-0310.2006.01283.x
|View full text |Cite
|
Sign up to set email alerts
|

First‐Year Common Nightingales (Luscinia megarhynchos) Have Smaller Song‐Type Repertoire Sizes Than Older Males

Abstract: Based on the assumptions that birdsong indicates male quality and that quality is related to age, one might expect older birds to signal their age. That is, in addition to actual body condition, at least some song features should vary with age, presumably towards more complexity. We investigated this issue by comparing repertoire sizes of free‐ranging common nightingale males in their first breeding season with those of older males. Nightingales are a good model species as they are open‐ended learners, where s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
50
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(54 citation statements)
references
References 43 publications
4
50
0
Order By: Relevance
“…However, repertoire change with age has not been observed in some populations of the Great Reed Warbler (Forstmeier et al 2006), andKipper et al (2004) reported that Nightingale Luscinia megarhynchos males C2 years did not increase their repertoire size in the subsequent year. In a cross-sectional comparison, Kiefer et al (2006) showed that 1-year old males had smaller repertoires than older males. This result was confirmed by a subsequent longitudinal study (Kiefer et al 2009) showing that 1-year-old males had an increased repertoire the next year.…”
Section: Discussionmentioning
confidence: 98%
“…However, repertoire change with age has not been observed in some populations of the Great Reed Warbler (Forstmeier et al 2006), andKipper et al (2004) reported that Nightingale Luscinia megarhynchos males C2 years did not increase their repertoire size in the subsequent year. In a cross-sectional comparison, Kiefer et al (2006) showed that 1-year old males had smaller repertoires than older males. This result was confirmed by a subsequent longitudinal study (Kiefer et al 2009) showing that 1-year-old males had an increased repertoire the next year.…”
Section: Discussionmentioning
confidence: 98%
“…1 h spontaneous nocturnal singing; see the electronic supplementary material, figure S2, for an example of a song sequence). This sample size has been shown to be sufficient to approach the asymptote of repertoire curves in the species [36]. To analyse whether some song types were sung in transition more often than would be expected by chance, we determined a 'distance to chance x 2 ' value for each bird as follows: we generated a song type transition matrix with current rspb.royalsocietypublishing.org Proc.…”
Section: Methodsmentioning
confidence: 99%
“…A paired test revealed that males increased their repertoire, and thus song diversity, between successive years. Other studies on various bird species showed that the repertoire increases with age or at least between the first two breeding seasons (Nottebohm & Nottebohm 1978;Hiebert et al 1989;Lampe & Espmark 1994;Gil et al 2001;Forstmeier et al 2006;Kiefer et al 2006;Nicholson et al 2007). A large repertoire and high song diversity may thus reflect male age and indirectly indicate good genes that enabled the male to survive (Kokko & Lindstrom 1996;Kokko 1998;Brooks & Kemp 2001;Jennions et al 2001).…”
Section: Discussionmentioning
confidence: 99%